PENGARUH MOTIVASI, DISIPLIN, DAN ETOS KERJA TERHADAP KINERJA KARYAWAN DIKANTOR KECAMATAN SLAHUNG KABUPATEN PONOROGO - Agum Gumelar; Umi Farida; Edi Santoso (Gapenas Publisher, 2022)
The study aims to determine the efeect of motivation, discipline, and work ethnic on employee performance at the Slahung sub-district office, Ponorogo district. The sample in this study was 41 respondents. The tasting stage use include instrument testing, coefficient of determinationtest and hypothesis testing. The analysis in this study multiple linier regression analysis. The result of this study indicate that: (1) Motivation has a positive and significant effect on employee performance, as evidenced by the t-count value of 2.079>2.026 t table. While the significant value is 0.045<0.05. (2) Discipline has a positive and significant effect on employee performance, as evidenced by the t-count value of 2.061>2.026 t table. While the significant value is 0.046<0.05. (3) Work ethnic has a positive and significant effect on employee performance, as evidenced by the t-count value of 2.324>2.026 t table. While the significant value is 0.026<0.05. (4) Motivation, Discipline, and Work ethnic simultaneously have a posisitve and significant effect of employee performance as evidencend by the calculated F value of 7.541 > F table 2.86 and thesignificant value obtained is 0.000< 0.05